Feedbacks at School from Teachers? and Students? Perspectives - Bąk, Olga (INSTED: Interdisciplinary Studies in Education & Society, 2015)
Feedback received by students plays an important role in shaping students? academic progress, their ability to abide by certain rules and norms as well as their pro-social behaviours. The effectiveness of feedback depends on the way it is provided. The aim of this study was to determine what type of feedback is the most prevalent in the student-teacher communication. Provided feedback was analysed from two separate perspectives: students? and teachers?. Students (N = 271) and teachers (N = 65) from chosen high schools took part in the study. Teacher?s Feedbacks Questionnaire was used to obtain the respondents? opinions on the frequency of different types of feedback provided both in ?teaching situations? vs ?pedagogical situations? and with respect to positive vs negative behaviours. Thanks to the application of an appropriate procedure it was possible to obtain data regarding: 1) teachers? imagined expectations of students and 2) actual reactions (as declared individually). Students were tested in regards to: 3) their expectations towards feedback and 4/ actual feedback received from the teachers. The results show that, as for the positive feedback, teachers? beliefs towards what is expected by the students and what students actually expect were congruent, whereas it was opposite regarding the negative feedback. A clear discrepancy could also be seen between students? and teachers? opinions concerning the actual feedback provided for both positive and negative feedback. There is a clear tendency for teachers to present themselves as communicatively competent pedagogues, who provide effective and constructive feedback. Students, on the other hand, indicate that the student-teacher communication is lacking in terms of providing feedback